Latency Period after Preterm Premature Rupture of Membranes: Singletons versus Twins - Madden, Nigel; Andrikopoulou, Maria; Overton, Eve; Gyamfi-Bannerman, Cynthia (American Journal of Perinatology, 2021)
Objective Several studies have evaluated the differences in duration of latency and clinical outcomes between singleton and twin pregnancies after preterm premature rupture of membranes (PPROM); however, these data are limited to single-institution analyses and based on small sample sizes. The aim of this study was to assess differences in latency and clinical outcomes in singletons versus twin gestations affected by PPROM in a large, diverse cohort of women.Study Design This is a secondary analysis of a multicenter trial of magnesium for neuroprotection in women at high risk of preterm birth. Our study included women with PPROM ≥ 24 weeks with singleton and twin gestations. We compared singleton versus twin gestation and our primary outcome was duration of latency after PPROM. Secondary outcomes included selected perinatal and neonatal outcomes including long-term neurodevelopmental outcomes. We fit a linear regression model to assess independent risk factors for latency duration.Results Our study included 1,753 women, 1,602 singleton gestations (91%) and 151 twin gestations (9%). The median latency period was significantly shorter in twins (4 [interquartile range, IQR: 1–10] vs. 7 [IQR: 3–16] days, p < 0.001) and gestational age at delivery was significantly earlier (29.3 vs. 30.1 weeks, p = 0.001). Twins were more likely to develop neonatal sepsis (20.1 vs. 13.4%, p = 0.004), but rates of chorioamnionitis and abruption did not differ. Twins were more likely to suffer from adverse short-term neonatal outcomes, had higher rates of neonatal demise (7.9 vs. 3.8%, p = 0.002), and had higher rates of cerebral palsy (7.3 vs. 3.7, p = 0.005). When adjusting for confounders, twin gestation remained an independent risk factor for shorter latency (p < 0.001).Conclusion Twin gestations affected by PPROM had shorter latency, earlier delivery, and higher rates of short- and long-term morbidity. Despite having longer latency, singleton gestations did not have higher rates of complications associated with expectant management.Key Points
Keywords: PPROM; latency period; cerebral palsy; twin gestation